2022
DOI: 10.12998/wjcc.v10.i6.1795
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant organisms in intensive care units and logistic analysis of risk factors

Abstract: BACKGROUND Intensive care unit (ICU) patients are critically ill and have low immunity. They will undergo various trauma medical procedures during diagnosis and treatment. The use of high-dose hormones and broad-spectrum antibiotics will increase the incidence of nosocomial infection in ICU patients. Therefore, it is necessary to explore the causes of nosocomial infection in ICU and provide basis for the prevention and control of nosocomial infection in ICU. AIM To expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…The predominant species, isolated during the present study, were A. baumannii (18 isolates, 42.9%) followed by K. pneumoniae (16 isolates, 38.1%), E. coli (6 isolates, 14.3%) and P. stuartii (2 isolates, 4.7%). Similar results were demonstrated by Han et al 19 15 who reported that A. baumannii was resistant to carbapenems, aminoglycosides, most cephalosporins and sulfa containing antibiotics with resistance rates of > 75%. They also reported A. baumannii polymyxin sensitivity of 96.67%.…”
Section: Discussionsupporting
confidence: 87%
“…The predominant species, isolated during the present study, were A. baumannii (18 isolates, 42.9%) followed by K. pneumoniae (16 isolates, 38.1%), E. coli (6 isolates, 14.3%) and P. stuartii (2 isolates, 4.7%). Similar results were demonstrated by Han et al 19 15 who reported that A. baumannii was resistant to carbapenems, aminoglycosides, most cephalosporins and sulfa containing antibiotics with resistance rates of > 75%. They also reported A. baumannii polymyxin sensitivity of 96.67%.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this is the widespread use of antibiotics in the community before admission to the hospital in our country. The discussion of Han et al [ 1 ] of this high carbapenem and polymxin resistance in their study will add strength to their study.…”
Section: To the Editormentioning
confidence: 93%
“…We recently read with great interest the manuscript by Han et al [ 1 ] entitled “Multidrug-resistant organisms in intensive care units and logistic analysis of risk factors,’’ which was published in the last issue of World J Clin Cases . We would like to state that the article is very detailed, and we have benefited from it in many points.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations